2020
DOI: 10.1088/1748-9326/ab6d7f
|View full text |Cite
|
Sign up to set email alerts
|

Does elevation dependent warming exist in high mountain Asia?

Abstract: A majority of studies suggest that elevation dependent warming (EDW) has been verified in mountainous areas. However, there is some controversy about the EDW of high mountain Asia (HMA). Based on the analysis of the data from 128 meteorological stations in the entire region for 1961-2017, we found that there was no EDW in HMA on the time scale of 1961-2017 and the spatial scale of the altitude of 3500-5000 m. The EDW in HMA is the most obvious during the period of 1998-2012. In general, after 1980, there was E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 60 publications
(61 reference statements)
4
35
0
Order By: Relevance
“…However, EDW is not present in all sub-regions. Li et al (2020) similarly suggested that EDW only occurs in certain areas, which is consistent with our results (Figure 6). The most pronounced EDW and elevation-dependent variations of snow depth simultaneously occur in the southeastern TP, where the largest 5) difference in elevation from 2,000 to 6,000 m is located.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, EDW is not present in all sub-regions. Li et al (2020) similarly suggested that EDW only occurs in certain areas, which is consistent with our results (Figure 6). The most pronounced EDW and elevation-dependent variations of snow depth simultaneously occur in the southeastern TP, where the largest 5) difference in elevation from 2,000 to 6,000 m is located.…”
Section: Discussionsupporting
confidence: 93%
“…There is consensus regarding the overall enhanced warming of the TP, but the exact elevation profile of EDW is still controversial (You et al, 2008;Rangwala et al, 2009;Kang et al, 2010;You et al, 2010;Guo and Wang, 2012;Gao et al, 2018). For example, Li et al (2020) suggested that EDW has only occurred in specific mountainous ranges on the TP. It is expected that such regional EDW differences across the plateau could significantly impact the spatiotemporal characteristics of snow depth.…”
mentioning
confidence: 99%
“…Many studies 14,17,29,30 have shown that the transport of heat by atmospheric circulations reduces the temperature heterogeneity at the Earth's surface and this process also affects the regional climate. To determine which circulation has the greatest influence on the temperature in the three regions, we first analyze the correlation between the air temperature and 23 major atmospheric circulations (Supplementary Note 1) and 2 sea ice indexes (Supplementary Table 1a).…”
Section: Resultsmentioning
confidence: 99%
“…We use the Mann–Kendall statistical method to assess the significance of the mean temperature trends in the study area. The Mann–Kendall statistical test has been commonly used to assess the significance of monotonic trends in climatic series 30 . The Monte Carlo method 18 20 is used to estimate the field significance of the temperature cooling trend in the CEU.…”
Section: Methodsmentioning
confidence: 99%
“…At the regional scale, geomorphology, topography and land cover are known to affect the climate patterns to some extent (Pepin et al 2015;Bright et al 2017;Minder et al 2018;Aguilar-Lome et al 2019). Many studies have shown that regions of higher elevations are more susceptible to global climate change than regions of lower elevations (Pepin et al 2015;Li et al 2020aLi et al , 2020bYou et al 2020); with increases in elevation, the annual mean temperature and precipitation generally become more variable (You et al 2020;Li et al 2020aLi et al , 2020cAguilar-Lome et al 2019;Minder et al 2018;Pepin et al 2015). Topography may affect climate through interference to lower atmospheric circulation and air-flow dynamics (Jiang 2003;Barros et al 2006;Yang and Zhang 2019;He et al 2019).…”
Section: Introductionmentioning
confidence: 99%